Shark populations in Chatham and Wafer bays, Isla del Coco National Park, Costa Rica. - Zanella, Ilena; López-Garro, Andrés; Martínez, Frank; Golfín-Duarte, Geiner; Morales, Keylor (Revista de Biología Tropical, 2016)
At least fourteen species of sharks live in the Marine Protected Area of Isla del Coco National Park (ICNP), some are resident species such as the whitetip reef shark (Triaenodon obesus); others are migratory and visit the National Park throughout the year, e.g. the scalloped hammerhead shark (Sphyrna lewini) and the whale shark (Rhincodon typus). Between March 2010 and August 2012 six expeditions out to the ICNP were carried, during this period 25 night trips (from 18:00 to 22:00 hr) for shark tagging were conducted in the Wafer and Chatham bays. During those trips, 185 sharks were analyzed: 81.1 % were whitetip reef sharks (T. obesus), 16.7 % were blacktip sharks (Carcharhinus limbatus), 1.1 % were blacktip reef sharks (Carcharhinus melanopterus) and 1.1% were silvertip sharks (Carcharhinus albimarginatus). The most common species in Bahía Chatham was T. obesus, while the most common one in Bahía Wafer was C. limbatus, which represented 80.9 % and 80.5 % of the total sharks caught, respectively. Regarding T. obesus, a sex ratio of 1.2 males per female was estimated (X2=0.09; p=0.17); in turn a sex ratio of 1.01 males per female was observed (X2=0.04; p=0.79) for C. limbatus. The average total length for T. obesus and C. limbatus was 103.66±13.91 cm and 76.58±14.56 cm respectively; suggesting that black tip sharks use those bays during immature stages. The results show an interspecific spatial segregation of the most common resident sharks at ICNP, apparently the clear waters and the coral cover of Chatham Bay are preferred by T. obesus; while the turbid waters of the Genio River mouth are preferred by C. limbatus